(Pro)renin receptor contributes to regulation of renal epithelial sodium channel. Issue 3 (March 2016) - Quadri, Syed; Siragy, Helmy M.
Abstract : Background: Recent studies reported increased (Pro)renin receptor (PRR) expression during low-salt intake. We hypothesized that PRR plays a role in regulation of renal epithelial sodium channel (ENaC) through serum and glucocorticoid-inducible kinase isoform 1 (SGK-1)-neural precursor cell expressed, developmentally downregulated 4–2 (Nedd4–2) signaling pathway. Method: Male Sprague–Dawley rats on normal-sodium diet and mouse renal inner medullary collecting duct cells treated with NaCl at 130 mmol/l (normal salt), or 63 mmol/l (low salt) were studied. PRR and α-ENaC expressions were evaluated 1 week after right uninephrectomy and left renal interstitial administration of 5% dextrose, scramble shRNA, or PRR shRNA ( n  = 6 each treatment). Results: In-vivo PRR shRNA significantly reduced expressions of PRR throughout the kidney and α-ENaC subunits in the renal medulla. In inner medullary collecting duct cells, low salt or angiotensin II (Ang II) augmented the mRNA and protein expressions of PRR ( P  < 0.05), SGK-1 ( P  < 0.05), and α-ENaC ( P  < 0.05). Low salt or Ang II increased the phosphorylation of Nedd4–2. In cells treated with low salt or Ang II, PRR siRNA significantly downregulated the mRNA and protein expressions of PRR ( P  < 0.05), SGK-1 ( P  < 0.05), and α-ENaC expression ( P  < 0.05). Conclusion: We conclude that PRR contributes to the regulation of α-ENaC via SGK-1-Nedd4–2 signaling pathway. Abstract : Supplemental Digital Content is available in the text